Intestinal Drug Absorption Enhancement by Aloe vera Gel and Whole Leaf Extract: In Vitro Investigations into the Mechanisms of Action - Anja Haasbroek; Clarissa Willers; Matthew Glyn; Lissinda du Plessis; Josias Hamman (MDPI AG, 2019)
The co-administration of absorption enhancing agents with macromolecular drugs (e.g., protein and peptide drugs) has been identified as a means to improve the oral bioavailability of these drugs. Absorption-enhancing agents of natural origins have received a great deal of attention due to their sustainable production, in support of green chemistry. In previous studies, certain parts of the Aloe vera leaf (e.g., gel and whole leaf extract) have shown a potential to enhance drug permeation across the intestinal epithelial barrier. The mechanism of the drug-absorption-enhancement action and the capacity for absorption-enhancement of the A. vera gel and whole leaf, were investigated in this study. A clear decrease in transepithelial electrical resistance (TEER) of Caco-2 cell monolayers exposed to A. vera gel and wholeleaf extract, in various concentrations, indicated the opening of tight junctions between the epithelial cells. The transport of Fluorescein isothiocyanate (FITC)-dextran, with a molecular weight of 4 kDa (FD-4), could be enhanced across the Caco-2 cell monolayers, by the A. vera gel and whole-leaf extract, but not the FITC-dextran with larger molecular weights (i.e., 10, 20, and 40 kDa), which indicated a limited drug absorption enhancement capacity, in terms of the molecular size. Accumulation of FD-4 between the Caco-2 cells (and not within the cells), after treatment with the A. vera gel and whole-leaf extract was shown with a confocal laser scanning microscopy (CLSM) imaging, indicating that the paracellular transport of FD-4 occurred after the interaction of the A. vera gel and whole-leaf extract, with the epithelial cell monolayers. Furthermore, changes in the F-actin distribution in the cytoskeleton of the Caco-2 cell monolayers was observed by means of a fluorescence staining, which confirmed tight junction modulation as the mechanism of action for the absorption enhancement effect of the A. vera gel and whole-leaf extract.